2019
DOI: 10.3389/fpsyg.2018.02648
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Mind-Wandering Reader: Predictive Processing, Probability Designs, and Enculturation

Abstract: Studies on mind-wandering frequently use reading as an experimental task. In these studies, reading is conceived as a cognitive process that potentially offers a contrast to mind-wandering, because it seems to be task-related, goal-directed and stimulus-dependent. More recent work attempts to avoid the dichotomy of successful cognitive processes and processes of mind-wandering found in earlier studies. We approach the issue from the perspective that texts provoke modes of cognitive involvement different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 103 publications
(189 reference statements)
1
22
0
Order By: Relevance
“…In this type of task, the occurrence and maintenance of TUTs entails that top-down attention shifts from the text content to the individual's internal activity, causing a temporary mindless reading mode. Although recent approaches suggest that mindwandering could be beneficial to understand some passages of literary texts that, in fact, require the readers' mind to wander (see Fabry & Kukkonen, 2019 ), its detrimental consequences for reading comprehension have been widely reported ( Feng et al, 2013 ; McVay & Kane, 2012 ; Soemer & Schiefele, 2019 ; Unsworth & McMillan, 2013 ). The present study tests the hypothesis that shallow processing on screen is related to inattentive reading.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of task, the occurrence and maintenance of TUTs entails that top-down attention shifts from the text content to the individual's internal activity, causing a temporary mindless reading mode. Although recent approaches suggest that mindwandering could be beneficial to understand some passages of literary texts that, in fact, require the readers' mind to wander (see Fabry & Kukkonen, 2019 ), its detrimental consequences for reading comprehension have been widely reported ( Feng et al, 2013 ; McVay & Kane, 2012 ; Soemer & Schiefele, 2019 ; Unsworth & McMillan, 2013 ). The present study tests the hypothesis that shallow processing on screen is related to inattentive reading.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas this may be the case for informational, expository, and perhaps even some narrative texts, a reader of literary texts may adopt an entirely different goal, for example, reflecting on the underlying rhetorical structure or admiring the use of metaphor, irrespective of the actual narrative arc of the text. Fabry and Kukkonen (2019) suggested that investigating mind wandering during reading of literary texts might entail an entirely different research approach and proposed an alternate theoretical perspective of enculturated predictive processing than the standard models of comprehension (McNamara & Magliano, 2009). Whereas a traditional conceptualization of mind wandering as 'off-task thought' in most reading studies might be too vague to discriminate, for example, among processing the textual content versus the literary structure of a text, it does distinguish thoughts about laundry, an unrelated memory, or the room temperature, suggesting that perhaps the concern is a bit overstated.…”
mentioning
confidence: 99%
“…Implementation of clinical interventions takes place in a socio-cultural and organizational context, where procedures, norms, surrounding, interieur, experiences and expectations, affect cognitive processes [137,138], including ways in which HCPs perceive, interpret and make sense of both patient communication and of facilitatory intentions. Evidence derived from experimental studies of learning additionally suggests that learning (being a cognitive function/process) is an embodied activity and affected by multiple factors "spanning cognitive-emotional aspects (fatigue, hunger, lack of motivation) [139], external properties of the study environment (light, sound, ventilation, artefacts) [140,141] and embodied and socio-historical aspects (movement and social and experiential background [142][143][144]" (Trasmundi, personal communication 11.06.2020). We therefore need a more systematic knowledge about real-life clinical practices, including how internal (bodily)…”
Section: Discussionmentioning
confidence: 99%